2012
DOI: 10.1007/s00284-012-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dynamic Process Reduction of α- and β-Tetralone and Stereoinversion of Resulting Alcohols in a Selected Strain Culture

Abstract: α-Tetralone and β-tetralone were subjected to biotransformation by 14 fungal strains. Enantiomeric purity of the products depended on the reaction time. 3-Day transformation of α-tetralone in Absidia cylindrospora culture gave S-(+)-1,2,3,4-tetrahydro-1-naftol of 92 % ee, whereas longer biotransformation time resulted in decrease of ee value. 3-Day transformation of β-tetralone by the same strain gave predominantly S-(−)-1,2,3,4-tetrahydro-2-naftol, whereas after 9 days of the reaction, the R-enantiomer with 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In contrast to diaryl methanone, tetralones that carry different substituents belong to another series of bulky ketones (Figure ). The skeleton structure of these substrates is tetralin, a derivative of the fused ring compound naphthalene, the corresponding chiral alcohols of which are extremely valuable for the synthesis of many serotonin and dopamine agonists. Several microorganisms, including Absidia cylindrospora , Saccharomyces brasiliensis , and Chaetomium sp. can catalyze the reduction of 1-tetralones ( 65 ) and 2-tetralones ( 54 ) into corresponding ( S )-alcohols .…”
Section: Sources and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to diaryl methanone, tetralones that carry different substituents belong to another series of bulky ketones (Figure ). The skeleton structure of these substrates is tetralin, a derivative of the fused ring compound naphthalene, the corresponding chiral alcohols of which are extremely valuable for the synthesis of many serotonin and dopamine agonists. Several microorganisms, including Absidia cylindrospora , Saccharomyces brasiliensis , and Chaetomium sp. can catalyze the reduction of 1-tetralones ( 65 ) and 2-tetralones ( 54 ) into corresponding ( S )-alcohols .…”
Section: Sources and Propertiesmentioning
confidence: 99%
“…The skeleton structure of these substrates is tetralin, a derivative of the fused ring compound naphthalene, the corresponding chiral alcohols of which are extremely valuable for the synthesis of many serotonin and dopamine agonists. Several microorganisms, including Absidia cylindrospora , Saccharomyces brasiliensis , and Chaetomium sp. can catalyze the reduction of 1-tetralones ( 65 ) and 2-tetralones ( 54 ) into corresponding ( S )-alcohols . In 2002, Kroutil’s research group found 2-tetralone ( 54 ) can be reduced to corresponding ( S )-alcohol with 83% ee by lyophilized cells of Rhodococcus ruber DSM 44541 .…”
Section: Sources and Propertiesmentioning
confidence: 99%
“…26 It was reported that (S)-2 was manufactured with 100% ee using the biocatalyst of whole-cell Aquilegia coerulea KCh 93, but the conversion is very low (19%). 27 They also reported that with increasing reaction time, conversion increased, but ee decreased significantly. For example, after 9 days of reaction, (S)-2 was obtained in 76% yield, but in low ee (50%).…”
Section: Introductionmentioning
confidence: 96%
“…In the study performed with Pisum sativa whole‐cell biocatalyst, it was reported that ( S )‐2 was synthesized with 40% yield and 87% ee 26 . It was reported that ( S )‐2 was manufactured with 100% ee using the biocatalyst of whole‐cell Aquilegia coerulea KCh 93, but the conversion is very low (19%) 27 . They also reported that with increasing reaction time, conversion increased, but ee decreased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…For example, methoxy‐substituted 2‐tetralols have various degrees of biological importance through their ability to inhibit tubulin assembly . Enantiomerically pure ( S )‐2‐tetralol and its hydroxy and alkoxy analogs are used in the synthesis of various drugs that target many central nervous system disorders including 2‐aminotetralins, which exhibit dopamine‐receptor stimulating activity . ( S )‐6‐Chloro‐2‐tetralol is a main building block for the drug MK‐0499, which can be used as a potassium channel blocker for the treatment of ventricular arrhythmias or as a polarization mediator of cardiac tissues …”
Section: Introductionmentioning
confidence: 99%